America's Disenfranchised Why Restoring Their Vote Can Save the Soul of Our Democracy - Meade, Desmond (Brown Democracy Medal, 2021)
The Lawrence and Lynne Brown Democracy Medal, presented by the McCourtney Institute for Democracy at Penn State, recognizes outstanding individuals, groups, and organizations that produce innovations to further democracy in the United States or around the world. Voting is foundational in a democracy, yet over six million American citizens remain stripped of their ability to participate in elections. Once convicted of a felony, people who complete their sentences reenter society, but no longer with the civil rights they once had. They may return to school, secure employment to provide for their families, and become law-abiding, tax-paying citizens-sometimes for decades-and still be denied the voting rights afforded to every other citizen. Desmond Meade, director of the Florida Rights Restoration Coalition and a returning citizen himself, played an instrumental role in the landslide 2018 Amendment 4 victory in Florida, which used the ballot box to restore voting rights to 1.4 million Floridians with a previous felony conviction. Meade argues how, state by state, America can do better. His efforts in Florida present a compelling argument that creating access to democracy for those living on the fringes of society will create a more vibrant and robust democracy for all. He is the winner of the 2021 Brown Democracy Medal for his continuing work to restore voting rights and connect Americans along shared social values.